2021
DOI: 10.1093/ecco-jcc/jjab164
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and Outcome of Extranodal Primary Intestinal Lymphoma in Inflammatory Bowel Disease: An ECCO CONFER Case Series

Abstract: Background There is a small but measurable increased risk of lymphoma in inflammatory bowel disease (IBD), with a suggestion that primary intestinal lymphoma in IBD is associated with inflamed tissue and immunosuppressant use, mainly thiopurines. Methods This multicentre case series was supported by the European Crohn’s and Colitis Organisation (ECCO) and performed as part of the Collaborative Network of Exceptionally Rare ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…A retrospective multicentre case series by ECCO looked at 15 patients with PIL in IBD. It showed a strong male predilection for PIL in patients with IBD and diffuse large B-cell lymphoma as the most common histological type [36 ▪▪ ]. It also showed that in 60% of the cases (9/15), immunosuppression was being used and intestinal inflammation was associated with PIL in two-third of the patients [36 ▪▪ ].…”
Section: Lymphoma In Inflammatory Bowel Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…A retrospective multicentre case series by ECCO looked at 15 patients with PIL in IBD. It showed a strong male predilection for PIL in patients with IBD and diffuse large B-cell lymphoma as the most common histological type [36 ▪▪ ]. It also showed that in 60% of the cases (9/15), immunosuppression was being used and intestinal inflammation was associated with PIL in two-third of the patients [36 ▪▪ ].…”
Section: Lymphoma In Inflammatory Bowel Diseasementioning
confidence: 94%
“…It showed a strong male predilection for PIL in patients with IBD and diffuse large B-cell lymphoma as the most common histological type [36 ▪▪ ]. It also showed that in 60% of the cases (9/15), immunosuppression was being used and intestinal inflammation was associated with PIL in two-third of the patients [36 ▪▪ ]. The incidence rate (per 100 000 patient-years) of PIL in the general population in 0.5 vs. 12.1 in patients with IBD.…”
Section: Lymphoma In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Primary Intestinal Lymphoma (PIL) is a rare form of NHL that primarily affects the gastrointestinal tract, specifically the small intestine [81]. While PIL can occur in individuals without any underlying conditions, there is a notable association between PIL and IBD, particularly CD [81][82][83][84]. Four case series described this association [81][82][83][84].…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…While PIL can occur in individuals without any underlying conditions, there is a notable association between PIL and IBD, particularly CD [81][82][83][84]. Four case series described this association [81][82][83][84]. Phillips et al reported on fifteen IBD patients with PIL treated in eight different centers [81].…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…The important association of lymphoma and inflammatory bowel disease is a notable concern. There is a male predilection, in 2/3 of cases the patients were on immunosuppression and the lymphoma was also associated with areas of active disease [3]. Capsule endoscopy, deviceassisted enteroscopy and imaging are complementary and have been helpful towards reaching the diagnosis of this rare entity.…”
mentioning
confidence: 99%